Teachers’ Feedback and Trainees’ Confidence: Do They Match? - Haro Soler, María del Mar (Research in Language, 2021)
Due to the COVID-19 pandemic, traditional face-to-face learning was suddenly replaced by online learning in universities all over the world. This sudden switch posed a wide variety of challenges to teachers and students. This paper focuses on one teaching practice, teachers’ feedback, and on a students’ form of self-perception, self-efficacy beliefs, both inherent to the teaching-learning process, whether it occurs in the classroom or a virtual environment. An action-research mixed-method study was performed to analyze how teachers’ feedback can impact translation students’ self-efficacy beliefs in three educational modes: face-to-face lessons, blended learning and online learning. This study was performed in two phases. Firstly, a quasi-experimental field study was performed before the outbreak of the pandemic in three groups of the same course: one offered traditional classes, whereas the other two included blended learning. Following the essence of action-research, the results of this first phase were implemented in an online translation course during the pandemic. After comparing and contrasting the results obtained in these two phases, we can conclude that indirect, elaborate and dialogic feedback fostered the students’ self-efficacy beliefs, irrespective of the educational mode.